The Spillover Effect of Financial Agglomeration on Urbanization: An Empirical Study in Southwestern China - Liu, Xinyu (Asia Pacific Economic and Management Review, 2026)
To investigate the spillover effect of financial agglomeration, this study selected 46 prefecture-level cities in Southwest China from 2011 to 2020 as research subjects. The research applies Moran’s Index correlation test, using spatial econometric models for association analysis. Results show financial agglomeration has a pronounced spatial correlation with urbanization and the spillover effect of financial agglomeration enhances the development of urbanization. This study provides empirical support for policymakers in Southwest China to implement sustainable development goals for finance and urbanization.